Secrets of power negotiating : inside secrets from a master negotiator - Dawson, Roger, 1940- (Franklin Lakes, NJ : Career Press, 1999)
"Master negotiator Roger Dawson shows you how to make the most of all of your negotiations in the second edition of Secrets of Power Negotiating." "This comprehensive text, based on Dawson's best-selling audio cassette program, shows readers how to win negotiations and leave the other person feeling like he or she has actually won a key component of negotiations." "Secrets of Power Negotiating covers every aspect of the negotiating process with practical, proven advice: from beginning steps to critical final moves, how to recognize unethical tactics, key principles to the Power Negotiating strategy, why money is not as important as everyone thinks, negotiating pressure points, tips to negotiating with people from foreign lands, understanding the other party and gaining the upper hand, negotiating drives, and analyses of different negotiating styles. Book jacket."--Jacket
Playing the Power Negotiating Game -- Beginning Negotiating Gambits: -- Ask for More Than You Expect to Get -- Never Say Yes to the First Offer -- Flinch at Proposals -- Avoid Confrontational Negotiation -- The Reluctant Seller and the Reluctant Buyer -- Use the Vise Technique -- Middle Negotiating Gambits: -- Handling the Person Who Has No Authority to Decide -- The Declining Value of Services -- Never Offer to Split the Difference -- Handling Impasses -- Handling Stalemates -- Handling Deadlocks -- Always Ask for a Trade-off -- Ending Negotiating Gambits: -- Good Guy/Bad Guy -- Nibbling -- How to Taper Concessions -- The Withdrawing an Offer Gambit -- Positioning for Easy Acceptance -- Unethical Negotiating Gambits -- The Decoy -- The Red Herring -- Cherry Picking -- The Deliberate Mistake -- The Default -- Escalation -- Planted Information -- Negotiating Principles -- Get the Other Side to Commit First -- Acting Dumb is Smart -- Don't Let the Other Side Write the Contract -- Read the Contract Every Time -- Funny Money -- People Believe What They See in Writing -- Concentrate on the Issues -- Always Congratulate the Other Side -- Resolving Tough Negotiating Problems -- The Art of Mediation -- The Art of Arbitration -- The Art of Conflict Resolution -- Negotiating Pressure Points -- Time Pressure -- Information Power -- Being Prepared to Walk Away -- Take It or Leave It -- The Fait Accompli -- The Hot Potato -- Ultimatums -- Negotiating With Non-Americans -- How Americans Negotiate.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Negotiation in business; Négociations (Affaires); BUSINESS & ECONOMICS -- Negotiating; Negotiation in business; Management Styles & Communication; Management; Business & Economics